Evaluating the robustness effects of infrastructure projects based on their topological and geometrical roadway designs. (July 2017) - Snelder, M.; Wesseling, B.; van Arem, B.; Hertogh, M.J.C.M.
Abstract: When infrastructures projects are evaluated, it is not only important to evaluate them with models that represent the average daily situation, but also to evaluate them in case of irregular situations like incidents. This becomes especially relevant when various project alternatives are expected to show significantly different scores in case of incidents. Project alternatives and their road sections have different topological and geometrical characteristics. The focus of this paper is on the following characteristics: hard shoulders, the number of lanes, parallel road structures and weaving sections. The main question that this paper addresses is how these network characteristics affect both the risk of different types of incidents occurring and the effects of those incidents on the network performance (robustness). In order to answer this question, analytical examples are presented for small theoretical networks that give insight into how the selected characteristics affect the total delay caused by incidents and its dependence on the traffic volume, capacity, severity and duration of incidents. A marginal simulation based method is presented that can be used to compute the robustness effects of project alternatives, given their geometrical and topological characteristics, on a network level. A case study for an infrastructure project in the Netherlands is presented that illustrates how the robustness effects of infrastructure projects can be computed given their topological and geometrical characteristics. Highlights: Topological and geometrical characteristics affect the robustness of road networks. We focus on hard shoulders, number of lanes, parallel roads and weaving sections. Theoretical effects of these road characteristics on the robustness are shown. Robustness effects of infrastructure project alternatives are computed. A case study for Utrecht in the Netherlands is done.